Accountants of the future: what skills will be in demand in the post-pandemic era? / Wan Nailah Abdullah - Abdullah, Wan Nailah (Faculty of Accountancy, 2021)
The pandemic has resulted in business hibernation all over the globe. When hibernation period is over, there will be new demands for accountants to meet the needs in the post-crisis economy. Major recovery efforts are expected, and organisations will require different sets of skills from accountants to deal with the recovery. Here are some of the top skills or attributes for accountants to stay relevant in the post-COVID-19 pandemic.